1997
DOI: 10.1159/000213854
|View full text |Cite
|
Sign up to set email alerts
|

Influence of Visual Control, Conduction, and Central Integration on Static and Dynamic Balance in Healthy Older Adults

Abstract: Aging is associated with decreased balance abilities, resulting in an increased risk of fall. In order to appreciate the visual, somatosensory, and central signals involved in balance control, sophisticated methods of posturography assessment have been developed, using static and dynamic tests, eventually associated with electromyographic measurements. We applied such methods to a population of healthy older adults in order to appreciate the respective importance of each of these sensorial inputs in aging indi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

7
64
0
6

Year Published

2000
2000
2017
2017

Publication Types

Select...
6
2
1

Relationship

1
8

Authors

Journals

citations
Cited by 128 publications
(78 citation statements)
references
References 18 publications
7
64
0
6
Order By: Relevance
“…Participants stood on a forceplate (Equi+, model PF01; Aix les Bains, France) with eyes closed, arms at their sides and feet abducted at 30°with the medial borders of the heels separated by 5 cm. As vision is a predominant sensory system in the elderly (Perrin et al 1997), and as no significant effect of plantar cutaneous inputs could be seen when vision was available (Meyer et al 2004a), this information was suppressed in order to explore the influence of the cutaneous cues alone. Participants were asked to sway as little as possible.…”
Section: Walking Sessionmentioning
confidence: 99%
“…Participants stood on a forceplate (Equi+, model PF01; Aix les Bains, France) with eyes closed, arms at their sides and feet abducted at 30°with the medial borders of the heels separated by 5 cm. As vision is a predominant sensory system in the elderly (Perrin et al 1997), and as no significant effect of plantar cutaneous inputs could be seen when vision was available (Meyer et al 2004a), this information was suppressed in order to explore the influence of the cutaneous cues alone. Participants were asked to sway as little as possible.…”
Section: Walking Sessionmentioning
confidence: 99%
“…Due to the importance of vision and the oculomotor control involved in maintaining balance, closing the eyes during performance of balance tests increases sway both in a no alcohol condition (Hill and Steinhauer 1993b;Hill et (Ledin and Odkvist 1991). Results of these studies suggest the importance of vestibular and oculomotor integration.As is the case with other types of motor performance, balance appears to improve with age in children (Odenrick and Sandstedt 1984;Usui et al 1995) and decline with advancing age in older adults (Perrin et al 1997;Schultz et al 1997). In children, postural sway has been shown to decrease markedly between the ages of 3 and 5 years and then slowly after age 6, with boys showing more sway under the age of 10 than girls (Usui et al 1995).…”
mentioning
confidence: 91%
“…The influence of vision on equilibrium seems to be controversial. Some authors reported a greater postural sway in both planes after closing of the eyes [14,15]. In contrast, other researchers observed little effect or even its absence in postural sway [16].…”
Section: Discussionmentioning
confidence: 97%